The Relationship among Cronyism, Silence and Cynicism in Educational Organizations according to Teachers' Views - Turhan, Muhammed; Erol, Yusuf Celal (Hacettepe Univ, 2020)
Main aim of the research is to determine the relationships among cronyism, silence and cynicism in 20.07.2018 educational organizations. 7043 teachers working in Elazig city centre in 2016-2017 academic year constitute the population of the study. Using a simple random sampling method, study sample was formed. The data Accepted: were collected by using the Cronyism Scale, Cynicism Scale and Silence Scale. Cronyism scale is a 5 optioned 28.01.2019 Likert-type scale. The organizational cynicism scale consists of 9 items in Likert type with 5 options. The Silence Scale consists of one dimension, 3 items with 5 options-Likert type. 515 scale form was distributed to Online First: the teachers and 40 scale form had no return. 34 of them were not used in the study because they were not 01.02.2019 filled properly. Data of the remaining 441 scale forms are recorded in the SPSS program. Then, the data of 14 scale forms with missing data were deleted without being included in the analysis. According to the data of Published: the remaining 427 scale form, the data of 16 participants were not included in the statistical process 31.10.2020 considering the Skewness and Kurtosis values, extreme values, z values and Mahalonobis distance values. With the data of the remaining 411 scale form, the prerequisites for the analysis were obtained, it was seen that the data showed normal distribution and the analysis was started. With respect to the findings of the study, cronyism and cynicism perceptions of teachers were found to be moderate and silence perceptions were low. There was not any significant difference between female teachers and male teachers according to gender variables in their perceptions of cronyism. Organizational silence and cynicism perceptions of female teachers were significantly higher than male teachers. In addition, in education organizations, the perception of cronyism is a significant predictor of the level of organizational silence and cynicism. In line with these results, it is suggested that in education organizations, school administrators should avoid cronyism behaviors. It is of utmost importance that school administrators adopt a fair management approach to prevent teachers from exhibiting organizational silence and organizational cynicism attitudes and behaviors.
Öğretmen görüşlerine göre eğitim örgütlerinde kronizm, sessizlik ve sinizm arasındaki ilişki
Keywords: Cronyism; organizational silence; organizational cynicism